Українська та словацька ономастична фразеологія: проблеми перекладу - Кузь, Галина (My University, 2022)
The article discusses the topical issue of modern translation studies - the problem of adequate rendering of phraseology that reflects the national image of the world, in particular onomastic phraseology, ie phraseology with proper names. The aim of the work is a review analysis of phraseology with onomastic components of Ukrainian and Slovak languages in the context of their comparison and translation. This goal involves solving the following tasks: 1) to consider the types of proper names in the composition of phraseology; 2) analyze the types of onomastic phraseology; 3) identify the main difficulties in translating phraseological units with an onomastic component; 4) to characterize features of transformation of connotations of proper names as a part of phraseological units and a way of their translation. The analysis shows that in terms of the way of expressing cultural information, onomastic phraseology varies: it can be implemented through cultural meanings, cultural background and cultural connotations. The onym component is traditionally a cultural meaning in the composition of onomastic phraseology. The cultural background and cultural connotations of such units require ethnographic commentary: a simple translation is insufficient for an adequate perception of the text. Phraseologisms through names inform about important events, traditions, way of thinking, history and mythology of the ethnos. Proper names with their inherent cultural and historical connotations play an important role as a reference point in time and space. It should be noted that the borders between culturally specific and international onyms are becoming more and more mobile today due to the expansion and deepening of the processes of intercultural communication.
Ukrainian And Slovak Phraseology With Onomastic Component: Translation Problems
Keywords: onomastic phraseology, national image of the world, proper name, phraseology translation, Ukrainian and Slovakian translation.